2013
DOI: 10.1254/jphs.12283fp
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT1–Receptor Blockers Enhance Cardiac Responses to Parasympathetic Nerve Stimulation via Presynaptic AT1 Receptors in Pithed Rats

Abstract: Abstract. In the present study, we investigated the effects of angiotensin AT 1 -receptor blockers, KT3-671 and losartan, on the cardiac vagal neurotransmission in pithed rats. The bradycardia induced by vagal nerve stimulation (VNS, at 5 Hz) was potentiated significantly and dose-dependently by KT3-671 and also losartan. This enhancement effect of KT3-671 (10 mg/kg) was slightly potent than that of losartan (10 mg/kg). On the other hand, an angiotensin AT 2 -receptor blocker, PD123319 (10 mg/kg), did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…It is unlikely to be via the canonical G q/11 -AT1R coupling, which signals via the inhibition of cAMP and the generation of ROS, respectively [65]. These studies indicate that this pathway may be an additional mode of action via which Ang II blockers may be beneficial [57,59]. In conclusion, these data taken together indicate that losartan and other clinically available AT1R blockers potentiate vagal tone.…”
Section: Ang II Tonically Inhibits Cardiac Vagal Tone-peripheral Actionsmentioning
confidence: 75%
See 2 more Smart Citations
“…It is unlikely to be via the canonical G q/11 -AT1R coupling, which signals via the inhibition of cAMP and the generation of ROS, respectively [65]. These studies indicate that this pathway may be an additional mode of action via which Ang II blockers may be beneficial [57,59]. In conclusion, these data taken together indicate that losartan and other clinically available AT1R blockers potentiate vagal tone.…”
Section: Ang II Tonically Inhibits Cardiac Vagal Tone-peripheral Actionsmentioning
confidence: 75%
“…However, how far the losartan can diffuse out of the dialysis probe to the vagal nerve terminals could not be determined so a role for the postsynaptic receptors cannot be ruled out. These actions of Ang II on vagal tone appear to be mediated via AT1Rs since no effect on vagal stimulation-mediated bradycardia is observed with an AT2R antagonist [57].…”
Section: Ang II Tonically Inhibits Cardiac Vagal Tone-peripheral Actionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Òàêaeå äëÿ ñîåäèíåíèÿ KT3-671 ïîêàçàíà ñïîñîáíîñòü óñèëèâàòü ïàðàñèìïà-òè÷åñêîå âëèÿíèå íà ñåðäöå.  ñðàâíåíèè ñ ëîçàðòàíîì, äàííûé ïàðàñèìïàòèêî-ñòèìóëèðóþùèé ýôôåêò ïðàòîñàðòàíà ÿâëÿåòñÿ áîëåå âûðàaeåííûì [55]. Ó ïðîèçâîäíîãî èìèäàçî [5,4-b ]ïèðèäèíà L-158,809 áûëà âûÿâëåíà âûñîêîñåëåêòèâíàÿ AT 1 -àíòàãîíèñòè-÷åñêàÿ àêòèâíîñòü íà ìîäåëÿõ èçó÷åíèÿ ñèñòåìíîé ãåìîäèíàìèêè (ÀÄ, îáùåå ïåðèôåðè÷åñêîå ñîñóäèñòîå ñîïðîòèâëåíèå) è ôóíêöèè ñåðäöà (÷àñòîòà ñåðäå÷íûõ ñîêðàùåíèé, ñåðäå÷íûé âûáðîñ) ó íàðêîòèçèðîâàííûõ ãàëîòàíîì ñîáàê ñ çàêðûòîé ãðóäíîé êëåòêîé [40].…”
Section: ëèãàíäû At 1 -ðåöåïòîðîâunclassified
“…Recent studies in rats demonstrated evidence for presynaptic AT 1 receptors that can reduce parasympathetic responses to vagal stimulation by inhibiting ACh release (28). To test for the presence of this mechanism in guinea pigs, we determined the output frequency of intracardiac neurons from control animals with and without 100 nM ANG II in the bath solution.…”
Section: Effects Of Ang II Modulators In Healthy Animalsmentioning
confidence: 99%